Research in personnel and human resources management. Vol. 30 - Joshi, Aparna; Liao, Hui, 1975-; Martocchio, Joseph J. (Bingley, U.K. : Emerald, 2011)
This series publishes monograph length conceptual papers designed to promote theory and research on important substantive and methodological topics in the field of human resources management. Volume 30 of Research in Personnel and Human Resources Management (RPHRM) contains a collection of papers on important issues in the field of human resources management, including insights on employment branding, family owned firms, virtual global teams and intrinsic motivation, thus continuing the tradition of the series to develop a more informed understanding of the field. This collection of papers represents excellent scholarship and illustrates the truly interdisciplinary character of the field.
Global virtual teams : key developments, research gaps, and future directions / Luis L. Martins, Marieke C. Schilpzand -- An integration and extension of intrinsic motivation theories : the role of core affect / Matt Bloom, Amy E. Colbert -- Mindfulness at work / Theresa M. Glomb, Michelle K. Duffy, Joyce E. Bono, Tao Yang -- Socioemotional wealth and human resource management (HRM) in family-controlled firms / Cristina Cruz, Shainaz Firfiray, Luis R. Gomez-Meija -- An uncertainty reduction model of relational demography / Prithviraj Chattopadhyay, Elizabeth George, Carmen Kaman Ng -- Rebranding employment branding : establishing a new research agenda to explore the attributes, antecedents, and consequences of workers' employment branding knowledge / Timothy M. Gardner, Niclas L. Erhardt, Carlos Martin-Rios.
Keywords: Personnel management